The Role of Platelets in Myocardial Infarction, Ischemic Heart Disease, Cerebrovascular Disease, Thromboembolic Disorders and Acute Idiopathic Pericarditis - Zahavi, J (Thrombosis and Haemostasis, 1977)
Initial white thrombus formation, has been attributed to platelet interaction with damaged vessel wall at sites of vascular injury or atherosclerotic plaques in the process of platelet aggregation (PA) and adhesion. Enhancement of PA seems to be an important factor in the development of thrombosis in the coronary and cerebral blood vessels and in embolization of platelet microthrombi to the microcirculation of the vessels. This latter event in turn might lead to serious or fatal arrhythmias or to paroxysms of cerebral ischemia.We have found enhanced PA in 66 patients with acute myocardial infarction (MI) and ischemic heart disease (IHD) which was specifically indicated by 4 distinct abnormalities: a) increased rate and extent of aggregation to 11,1 μM of adenosine diphosphate (ADP). b) Increased platelet responsiveness to 1,11 μM of ADP. c) Spontaneous aggregation which appeared in 95% of the patients compared to less than 5% of controls, d) Prolonged aggregation time indicated by parameter τ, τ = -[dt/dln(T–T ∞ ≤)], In addition, enhanced and occasionally more pronounced PA on the day of discharge from hospital, has been recently observed. The abnormal platelet behaviour was also detected in 10 thromboembolic disorder (TED), 28 acute cerebrovascular accident (CVA) and 24 acute infectious disease (AI) patients. It was, however, more pronounced in MI compared to TED and CVA patients. In AI the curves returned to normal some time after their subsidence, but remained abnormal for up to 2 years in IHD patients. In 10 patients with acute benign idiopathic pericarditis, which were included in the AI patients, PA proved to be a rehable indicator of the course of the disease and its treatment. Early reduction of corticosteroid dosage in the patients, was followed by increased abnormalities in the PA curves.The enhanced PA in these patients is most probably an indicator of a thrombogenic state and seems to be an important contributory factor in the pathogenesis of coronary and cerebrovascular diseases. Preliminary reports of anti-aggregating drugs, wether beneficial or adverse, in these vascular disorders are controversial and further research is needed.